Studying Information Acquisition in the Field: A Practical Guide and Review - Francesco Capozza; Ingar Haaland; Christopher Roth; Johannes Wohlfart (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2021)
We review the emerging literature on information acquisition in field settings. We first document an increase in studies on information acquisition and review relevant studies in different subfields of economics, including macroeconomics, political economy, labor economics, health economics, and finance. We next provide an overview of empirical techniques to measure information acquisition and discuss the advantages and disadvantages of different methods. We then discuss how one can design studies to test the predictions of different theories of information acquisition. We conclude by highlighting possible directions for future research.
Keywords: C90; D83; D91; 330; information acquisition; willingness to pay; click data; experimental design; beliefs; surveys